Estereótipos dos suspeitos e ação policial : expressões e consequências - Poderoso, Emília Silva (2018)
A police approach usually starts with the traditional sentence "Stop, it's the police!" All the following procedures are, in principle, defined as "security measures" learned during professional qualification as "approach technique", present in practically all programs and military training. Although the procedures of the police approach are pre-defined in technical training manuals, the definition of who will be approached is an open question, influenced by factors internalized many times in automatic processes, without conscious control, and comes from a representation of the suspect, which affects social judgments. With that, this work aims to analyze the stereotypes that the military police of the State of Sergipe have about the suspect and its implications in the police activity. The research was composed by three studies. Study 1 examined the stereotypes police officers attribute to suspects considering their skin color and social status. Studies 2 and 3, using a technique of analysis of automatic response processes, analyzed the shooting decision on armed or disarmed suspects, whites or blacks, Military Police officers in the early stages of professional training or others with ten years or more of professional performance. The results of Study 1 indicate that there is an association between poverty and suspicion, on the one hand, and between skin color and poverty on the other. Studies 2 and 3 indicated the presence of "shooter bias", that is, the tendency to shoot faster and more accurately on black armed suspects than white suspects; as well as the quickest decision not to shoot unarmed suspects of white color than black. The results are discussed in light of the theories of social and cognitive psychology.